Assessing the feasibility and acceptability of Changing Health for the management of prediabetes: protocol for a pilot study of a digital behavioural intervention - Sophie Cassidy (Pilot and Feasibility Studies, 2019)
Abstract Background The prevalence of prediabetes is rapidly rising in the UK, largely associated with an increase in obesity. Lifestyle programmes that provide support to make and sustain dietary and physical activity behavioural changes are necessary to initiate and maintain weight loss. However, these programmes are often intensive and time consuming. Given the magnitude of the problem, there is a need for behavioural interventions that can be delivered at scale. Digital interventions can address some of the aforementioned issues. The primary aim of the present study is to assess the feasibility and acceptability of a digital intervention called Changing Health that provides structured education and lifestyle behaviour change support to adults with prediabetes. Methods A single-group pilot study will be undertaken. We aim to recruit 40 participants with prediabetes defined by HbA1c or fasting plasma glucose (FPG), aged between 18 and 75 years with a BMI ≥ 25. Participants will receive the digital intervention (a mobile phone app incorporating structured education and behavioural tools to support lifestyle behaviour change) with the aim of losing and maintaining 5–6% of their baseline body weight. Each participant will receive 100 min of lifestyle coaching over the 9-month intervention period and will have continued access to the digital intervention. Clinical outcome measures will be collected during four visits to our clinical research facility: two visits at baseline, one visit at month 3, and one visit at month 9. These secondary outcome measures will include diet, physical activity, sleep, metabolic control, body composition, cardiorespiratory fitness, and cardiovascular function. To measure primary outcomes, an embedded qualitative study will be conducted to obtain data on feasibility and acceptability of the intervention. Discussion This pilot study will establish whether Changing Health is feasible and acceptable to adults with prediabetes. Clinical outcome measures will provide estimates of variability to inform sample size calculations, and qualitative data generated will inform any necessary refinements to the intervention. This will provide a platform for a larger evaluation to assess the effectiveness of Changing Health for changing diet and physical activity to initiate and maintain weight loss in adults with prediabetes. Trial registration ISRCTN Registry: ISRCTN69270299.